2017
DOI: 10.1007/s00381-017-3610-z
|View full text |Cite
|
Sign up to set email alerts
|

A clinical scoring system to predict the development of intraventricular hemorrhage (IVH) in premature infants

Abstract: Low gestational age (GA), low Apgar score, and having bleeding diathesis were the most important risk factors for IVH. According to these risk factors, a scoring system was developed for IVH ranged from 0 to 5. According to the risk ratios (RR) obtained from the logistic regression model, low GA (≤ 28 gestational week), presence of bleeding diathesis within 7 days, and low Apgar score increased the risk of IVH (RR = 3.32 for GA ≤ 28 gestational week, RR = 6.7 for presence of bleeding diathesis in 7th day, RR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
2
26
0
3
Order By: Relevance
“…GMH-IVH infants had a significantly lower GA and Apgar score compared to controls. This is consistent with previous data investigating the predictive risk factors for GMH-IVH development (22,23). Although an inverse correlation between TOHRx and GA has been previously reported (12), in the present study the between-group difference was observed only before, and not after GMH-IVH development.…”
Section: Discussionsupporting
confidence: 93%
“…GMH-IVH infants had a significantly lower GA and Apgar score compared to controls. This is consistent with previous data investigating the predictive risk factors for GMH-IVH development (22,23). Although an inverse correlation between TOHRx and GA has been previously reported (12), in the present study the between-group difference was observed only before, and not after GMH-IVH development.…”
Section: Discussionsupporting
confidence: 93%
“…Neuroprotective interventions have been tested to reduce PIVH incidence and its severity 7 , 8 . The prophylactic use of antenatal corticosteroids (e.g., a complete course of betamethasone) reduced the incidence of PIVH in neonates 7 , 10 , 43 . However, repeated antenatal glucocorticoid courses can cause adverse effects on fetal growth and cerebral cortical maturation 7 without further reducing the incidence of PIVH 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Peri-intraventricular hemorrhage (PIVH) is one of the most serious prematurity-related illnesses 5 , 6 because of its incidence (15–30% of infants born at less than 32 weeks’ gestational age) and the severity of brain injury 7 , 8 . The incidence of PIVH is inversely proportional to the gestational age and the newborn weight 3 , 9 , 10 , with a higher risk in male newborns 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations